L’écriture de l’impuissance dans Die Liebesblödigkeit de Wilhelm Genazino - Anne-Sophie Hillard (Recherches Germaniques)
Wilhelm Genazino’s novel Die Liebesblödigkeit (2005) depicts the inner journey of the narrator and protagonist torn by his love for two women and his inability to choose between one of them. This indecision corresponds to a general feeling of powerlessness which is linked to his fear of death, omnipresent in the narration, a feeling reflected in the objects and events described by the narrator, which officiate as a reflection of his subjectivity. Thus, this inner monologue, centered on vision, performs a spatialization of the narration. The narrator offers the reader his point of view, provides him with his subjectivity by appropriating objects that become the vessel of his inner revelation. The subjectivity of the narrator, caused by a loss of contact with reality, is deeply connected with the question of identity and is revealed through the motif of powerlessness. The article analyzes to what extent this text is a discussion about identity and its continuity, and in what way psychological, ontological powerlessness (and physical impotence) precisely leads to a process of spatialization and of horizontality, creating the possibility for a (re)construction of the subject’s identity.